Heterozygous app a713t mutation carrier with inflammatoy amyloid angiopathy and family history of alzheimer´s disease: First case in Argentina - Fernández Suárez, Marcos Nicolás (2019)
Aim: To report the case of a patient who suffered from cerebral amyloid angiopathy due to an autosomal dominant mutation in the APP gene Design/Methods: Medical record and neuroimaging revision. DNA extraction from the saliva sample. Sanger sequencing of the coding regions of the following: APP (NCBI RefSeq NM_000484.3), PSEN1 (NCBI RefSeq NM_000021.3) y PSEN2 (NCBI RefSeq NM_000447.2) Clinical case: A male patient of 71-year-old with a past medical history of recurrent lobar hemorrhagic strokes leading to major cognitive decline since the age of 65, prominent cerebral microangiopathy was present and worsened progressively. Patient´s mother had presenile Alzheimer`s disease. The patient developed partial nonconvulsive status epilepticus, no evidence of new strokes (ischemic or hemorrhagic) was found. Two weeks after seizures a new MRI unveiled right frontal meningeal enhancement. Lumbar puncture and cultures were normal. Inflammatory amyloid angiopathy was suspected. A course of IV methylprednisolone was administered followed by oral steroids with a slight improvement. The patient died four months after due to clinical complications. Post-mortem analysis confirmed a heterozygous mutation: c.2137G>A; p.Arg713Thr at exon 17 of the APP gene. Conclusion: The A713T mutation has been reported by groups of European researchers (British, Spanish and Italian) with variable phenotypes. This would be the first case detected in Argentina to our knowledge. It is notable the main manifestation in our case was the presence of recurrent hemorrhagic stroke, however, the antecedent of a pre-senile AD in a first-degree relative suggested the presence of genetic etiology. This mutation may be underdiagnosed. It would be advisable that a complete genogram must be performed in patients with cerebral amyloid angiopathy. The detection of these cases has implications for genetic counselling.